2018
DOI: 10.1111/cas.13548
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐human SIRPα antibody is a new tool for cancer immunotherapy

Abstract: Interaction of signal regulatory protein α (SIRPα) expressed on the surface of macrophages with its ligand CD47 expressed on target cells negatively regulates phagocytosis of the latter cells by the former. We recently showed that blocking Abs to mouse SIRPα enhanced both the Ab‐dependent cellular phagocytosis (ADCP) activity of mouse macrophages for Burkitt's lymphoma Raji cells opsonized with an Ab to CD20 (rituximab) in vitro as well as the inhibitory effect of rituximab on the growth of tumors formed by Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
(106 reference statements)
1
39
0
Order By: Relevance
“…This Ab to human SIRPα also increased the phagocytic activity of macrophages from hSIRPα Tg mice, but not that of those from Rag2 −/− Il2rg −/− mice, as measured in vitro with human cancer cells opsonized with Abs to tumor antigens, suggesting that the interaction of human CD47 on human cancer cells with human SIRPα on mouse macrophages generates an inhibitory signal for macrophage ADCP. Moreover, in both of these genetically modified mouse models transplanted with human tumor cells, the antitumor effects of the Abs to human SIRPα were found to be dependent, at least in part, on macrophages . These mice may thus serve as models for preclinical validation of Abs to human SIRPα in cancer immunotherapy (Figure ).…”
Section: Xenograft Tumor Models For Preclinical Validation Of the Antmentioning
confidence: 97%
See 1 more Smart Citation
“…This Ab to human SIRPα also increased the phagocytic activity of macrophages from hSIRPα Tg mice, but not that of those from Rag2 −/− Il2rg −/− mice, as measured in vitro with human cancer cells opsonized with Abs to tumor antigens, suggesting that the interaction of human CD47 on human cancer cells with human SIRPα on mouse macrophages generates an inhibitory signal for macrophage ADCP. Moreover, in both of these genetically modified mouse models transplanted with human tumor cells, the antitumor effects of the Abs to human SIRPα were found to be dependent, at least in part, on macrophages . These mice may thus serve as models for preclinical validation of Abs to human SIRPα in cancer immunotherapy (Figure ).…”
Section: Xenograft Tumor Models For Preclinical Validation Of the Antmentioning
confidence: 97%
“…In this regard, a blocking Ab to human SIRPα was recently shown to promote the antitumor effects of rituximab and of vorsetuzumab (an Ab to CD70) in human tumor-bearing Rag2 −/− Il2rg −/− immunodeficient mice in which the DNA sequence encoding the extracellular domain of mouse SIRPα was replaced with the corresponding human sequence (hSIRPα KI mice) 63,64. With the use of Rag2 −/− Il2rg −/− mice expressing human SIRPα under the control of human regulatory elements (hSIRPα Tg mice),65 we also showed that a blocking Ab to human SIRPα enhanced the inhibitory effect of rituximab on the growth of tumors formed by s.c. injected Raji cells 66. This Ab to human SIRPα also increased the phagocytic activity of macrophages from hSIRPα Tg mice, but not that of those from Rag2 −/− Il2rg −/− mice, as measured in vitro with human cancer cells opsonized with Abs to tumor antigens, suggesting that the interaction of human CD47 on human cancer cells with human SIRPα on mouse macrophages generates an inhibitory signal for macrophage ADCP.…”
mentioning
confidence: 89%
“…Phase I clinical trials involving single agent administration of monoclonal antibodies blocking the CD47‐SIRPα include humanized CD47‐blocking agents such as Hu5F9‐G4, CC‐90002, and SIRPα protein variants such as TTI‐621 and ALX148 . Clinical trial evidence increasingly points to limited anticancer efficacies associated with these therapies owing to limitations such as subpar binding affinities of SIRPα antibodies and systemic toxicities involving anti‐CD47‐based therapies …”
mentioning
confidence: 99%
“…As the reports that the SIRPα antibody markedly enhanced the inhibitory effect of rituximab on the growth of tumors formed by Raji cells [27], KWAR23 as one anti-SIRPα antibody was also a promising candidate for combination therapies to facilitate rapid and complete elimination of tumors [28]. These studies suggested that inhibiting SIRPα may also be more effective in treating cancers.…”
Section: Discussionmentioning
confidence: 90%